Editor's Introduction: Expand Your Mind Here! - Barron, Bruce (Evangelical review of theology, 2024)
An introduction is presented in which the editor discusses the tendency among Christians to limit their reading to materials that align with their own beliefs, urging for a broader engagement with diverse perspectives.